Application of the adaptive center-weighted vector median framework for the enhancement of cDNA microarray images - Lukac, Rastislav; Smołka, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
In this paper a novel method of noise reduction in color images is presented. The new technique is capable of attenuating both impulsive and Gaussian noise, while preserving and even enhancing the sharpness of the image edges. Extensive simulations reveal that the new method outperforms significantly the standard techniques widely used in multivariate signal processing.
Keywords: DNA microarray images; multichannel image processing; order-statistic theory; vector filters; impulsive noise